2016
DOI: 10.1177/1971400915621325
|View full text |Cite
|
Sign up to set email alerts
|

Brain MRI abnormalities in the adult form of myotonic dystrophy type 1: A longitudinal case series study

Abstract: This study aimed to verify whether brain abnormalities, previously described in patients with myotonic dystrophy type 1 (DM1) by magnetic resonance imaging (MRI), progressed over time and, if so, to characterize their progression. Thirteen DM1 patients, who had at least two MRI examinations, were retrospectively evaluated and included in the study. The mean duration (± standard deviation) of follow-up was 13.4 (±3.8) years, over a range of 7-20 years. White matter lesions (WMLs) were rated by semi-quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 64 publications
2
19
0
2
Order By: Relevance
“…Indeed, in most neurogenerative diseases (e.g., Alzheimer's Disease, Parkinson's Disease) the prevalence of the affected population significantly increases from the age of 60-65. 30 The idea of accelerated brain degeneration in DM1 was first described by Conforti et al, 8 who found an increase in brain atrophy, as measured by the ventricular/brain ratio. However, these results contrast with other attempts at longitudinal MRI assessment that found no loss over a period of 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in most neurogenerative diseases (e.g., Alzheimer's Disease, Parkinson's Disease) the prevalence of the affected population significantly increases from the age of 60-65. 30 The idea of accelerated brain degeneration in DM1 was first described by Conforti et al, 8 who found an increase in brain atrophy, as measured by the ventricular/brain ratio. However, these results contrast with other attempts at longitudinal MRI assessment that found no loss over a period of 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…While Gliem et al 7 did not find a greater volume loss over time in DM1 for either gray or white matter tissue, Conforti et al found a progression in white matter lesions along with greater brain atrophy assessed by the ventricular/brain ratio. 8 The aim of this study was to longitudinally assess the structural brain changes of DM1 patients over a period of more than 9 years and to delineate the pathway of disease progression. Additionally, we aimed to examine the potential genetic, muscular, clinical, and cognitive markers of this progression.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Parkinson’s is characterized by the loss of dopaminergic neurons in the substantia nigra (Shulman et al, 2011) and Huntington disease for loss of medium spiny neurons in the striatum (Vonsattel et al, 2011). Although CNS features in DM, including executive function deficits, are highly problematic for patients and white matter abnormalities are detected by MRI and pathological examination (Minnerop et al, 2011; Ogata et al, 1998), routine pathological findings are diffuse and previous reports suggest findings are non-specific (Conforti et al, 2016; Wozniak et al, 2013; Wozniak et al, 2014; Wozniak et al, 2011; Zanigni et al, 2016). The discovery that LPAC and QAGR tetrapeptide proteins accumulate in DM2 provides a new opportunity to understand the impact of the DM2 expansion mutation on the brain and to look for pathological findings at sites of RAN protein accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies adopting tractography evaluation ( Minnerop et al, 2011 , Wozniak et al, 2014 ) provide data showing microstructural WM damage in interhemispheric, corticospinal and limbic pathways and in frontal, temporal, parietal and occipital lobes. To date, only one study demonstrates that brain atrophy and white matter involvement are progressive over time in DM1 ( Conforti et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%